2022
DOI: 10.3390/rs14184576
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation, Driving Mechanism and Predictive Study of Total Column Ozone: A Case Study in the Yangtze River Delta Urban Agglomerations

Abstract: Total column ozone (TCO) describes the amount of ozone in the entire atmosphere. Many scholars have used the lower resolution data to study TCO in different regions, but new phenomena can be discovered using high-precision and high-resolution TCO data. This paper used the long time, high accuracy, and high-resolution MSR2 dataset (2000−2019) to analyze the spatial and temporal variation characteristics of TCO over the Yangtze River Delta Urban Agglomeration to explore the relationship between the TCO and meteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…et al [7] quantified the vertical ozone variability at different time scales using ozone data from Dobson measurements in the downtown Beijing and Xianghe suburban areas and found that the ozone single-peak and Dobson-based total column ozone exhibited consistent sinusoidal monthly variations, with a maximum value of 380 Dobson units (DU) in March and a minimum value of 305 DU in October. Based on the global TCO data of a global multi-sensor reanalysis (MSR2), Zhou, P. et al [8] studied the temporal and spatial variation characteristics of TCO in the Yangtze River Delta region of China from 2000 to 2019 and the correlation between it and related meteorological factors, populations, and industrial output values. They found that TCO is significantly higher in spring than in other seasons and the correlation between annual changes of TCO and meteorological factors is weak, indicating that it is affected by the game interaction of different external driving factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…et al [7] quantified the vertical ozone variability at different time scales using ozone data from Dobson measurements in the downtown Beijing and Xianghe suburban areas and found that the ozone single-peak and Dobson-based total column ozone exhibited consistent sinusoidal monthly variations, with a maximum value of 380 Dobson units (DU) in March and a minimum value of 305 DU in October. Based on the global TCO data of a global multi-sensor reanalysis (MSR2), Zhou, P. et al [8] studied the temporal and spatial variation characteristics of TCO in the Yangtze River Delta region of China from 2000 to 2019 and the correlation between it and related meteorological factors, populations, and industrial output values. They found that TCO is significantly higher in spring than in other seasons and the correlation between annual changes of TCO and meteorological factors is weak, indicating that it is affected by the game interaction of different external driving factors.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation coefficient for the TCO and sulfur dioxide emissions reached 0.59 and the correlation coefficient for nitrogen oxide emission reached 0.60. (8) This study used the SARIMA model to predict the TCO of China. Considering the seasonality and other characteristics of the data, the data were pre-processed and then trained with the AIC information criterion to find the best model parameters.…”
mentioning
confidence: 99%